2013
DOI: 10.11622/smedj.2013126
|View full text |Cite
|
Sign up to set email alerts
|

Is semen polymorphonuclear leucocytes count a good predictor of male genital tract infection?

Abstract: (1) Leucocytospermia often indicates an inflammatory condition, and is associated with possible infection and poor sperm activity. Bezold et al (2) have concluded that bacteriospermia, especially in sexually transmitted diseases, is a likely cause of male infertility and may jeopardise the pregnancy rate for in vitro fertilisation (IVF).Therefore, the detection of bacteriospermia is of high importance.Cumming and Carrell have concluded that it is more costeffective and prudent to first perform reflexive cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…[12] Numerous studies have shown that leukocytes are powerful producers of reactive oxygen species (ROS) and may have detrimental effects on sperm function and sperm DNA integrity. [1314] Despite the WHO[4] recognizing that the presence of leukocytes is indicative of an infection, several studies[1516] found that the detection of leukocytospermia and asymptomatic bacteriospermia is of no diagnostic value for the identification of men with acute bacterial infections and abnormal semen parameters, respectively. Reasons for this unexpected finding might be a possible delay in the deleterious actions of ROS produced by leukocytes due to their neutralization by antioxidants.…”
Section: Factors Influencing the Fertility Potential Of Spermatozoamentioning
confidence: 99%
“…[12] Numerous studies have shown that leukocytes are powerful producers of reactive oxygen species (ROS) and may have detrimental effects on sperm function and sperm DNA integrity. [1314] Despite the WHO[4] recognizing that the presence of leukocytes is indicative of an infection, several studies[1516] found that the detection of leukocytospermia and asymptomatic bacteriospermia is of no diagnostic value for the identification of men with acute bacterial infections and abnormal semen parameters, respectively. Reasons for this unexpected finding might be a possible delay in the deleterious actions of ROS produced by leukocytes due to their neutralization by antioxidants.…”
Section: Factors Influencing the Fertility Potential Of Spermatozoamentioning
confidence: 99%
“…Similarly, Gallegos et al (2008) observed that patients with GM had increased sperm DNA damage despite the absence of leucocytospermia. The finding of low levels of leucocytes in infected samples is not altogether unexpected as previous studies indicated leucocyte concentrations are poorly predictive of seminal microorganisms (Chen et al, 2013; Hillier et al, 1990). Furthermore, OS associated with chronic prostatitis is independent of leucocytospermia (Nickel et al, 2003; Pasqualotto et al, 2000).…”
Section: Discussionmentioning
confidence: 61%
“…1 This association remains controversial since high concentrations of semen leukocytes were also reported in the absence of inflammatory symptoms or microbial infection. 2 Although semen leukocytes are essential to remove pathogens and abnormal cells from seminal fluid, their presence at high concentrations can hurt semen quality. Some studies suggested that LCS decreased sperm motility and count while others reported a high frequency of altered spermatozoon associated with LCS.…”
Section: Introductionmentioning
confidence: 99%